Effectiveness of eccentric overload training in basketball players: a systematic review - Younes-Egana, O.; Mielgo-Ayuso, J.; Stojanovic, M.; Bird, S.; Calleja-González, J. (Journal of Human Kinetics, 2023)
Several studies have confirmed the efficacy of flywheel eccentric overload training in order to improve or increase muscle volume and strength, as well as several performance-related fitness attributes, but to date, there are no studies that have reviewed the effects of these training methods in basketball. Therefore, the present systematic review aimed to collect the updated information about the influence of flywheel training on performance of basketball players. A search in four electronic databases (PubMed, SCOPUS, Web of Science, and Google Scholar) was conducted up to November 20, 2022. Articles were selected as valid for review if: (i) they were an experimental trial published in English; (ii) participants were basketball players without illnesses or injuries, and (iii) a rotational inertial overload method was used as a performance-dependent variable. A total of 93 articles were found. After filtering procedures, only seven studies were considered in this systematic review. In the selected studies, 203 participants were included, 58 females and 145 males. Focusing on basketball related performance variables, all the studies included the countermovement jump (CMJ), while five included sprinting and a change of direction test (COD). The results showed an improvement in performance-related variables associated with basketball (sprint, CMJ, and COD) through the use of inertial methods. Improvements were reported in professional, semi-professional and amateur players as well as both male and female players. However, given the low number of studies, additional investigations on this topic are warranted before a "clear picture" can be drawn concerning the effects of flywheel eccentric overload training in basketball players.